2017
DOI: 10.1002/ece3.3455
|View full text |Cite
|
Sign up to set email alerts
|

The role of species‐specific sensory cues in male responses to mating rivals in Drosophila melanogaster fruitflies

Abstract: Complex sets of cues can be important in recognizing and responding to conspecific mating competitors and avoiding potentially costly heterospecific competitive interactions. Within Drosophila melanogaster, males can detect sensory inputs from conspecifics to assess the level of competition. They respond to rivals by significantly extending mating duration and gain significant fitness benefits from doing so. Here, we tested the idea that the multiple sensory cues used by D. melanogaster males to detect conspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 70 publications
(107 reference statements)
0
14
1
Order By: Relevance
“…In our study, males did not seem to distinguish between con‐ and heterospecific social partners as they respond to both similarly by increasing their song bout duration. This contrasts with recent findings showing that D. melanogaster males increase their mating duration to a lesser extent after being raised with D. simulans males than with D. melanogaster males (Bretman et al, ), suggesting that the response may be finely tuned to species identity for some but not all traits. Both species are commonly co‐collected with standard Drosophila trapping techniques and mixed species mating encounters have been described, but the likelihood and intensity of these mixed species interactions during development or courtship behavior in the field is not well understood (Gromko & Markow, ).…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In our study, males did not seem to distinguish between con‐ and heterospecific social partners as they respond to both similarly by increasing their song bout duration. This contrasts with recent findings showing that D. melanogaster males increase their mating duration to a lesser extent after being raised with D. simulans males than with D. melanogaster males (Bretman et al, ), suggesting that the response may be finely tuned to species identity for some but not all traits. Both species are commonly co‐collected with standard Drosophila trapping techniques and mixed species mating encounters have been described, but the likelihood and intensity of these mixed species interactions during development or courtship behavior in the field is not well understood (Gromko & Markow, ).…”
Section: Discussioncontrasting
confidence: 93%
“…Males raised with con‐ or heterospecific social partners produced courtship song with unchanged parameters, that is, similar IPI and SSF. Recent findings suggest that that D. melanogaster males can distinguish conspecific from D. simulans males (Bretman et al, ). This finely tuned response to species identity contrasts with the inflexibility of IPI and SSF we found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be achieved by the processing of multiple cue components. Subsequently, it has been shown that interfering with one cue alters the magnitude of off-target responses to heterospecific males (Bretman et al 2017), providing some evidence that multiple cues indeed enable better environmental matching.…”
Section: Hypotheses For the Benefits Of Complex Cue Use In Social Andmentioning
confidence: 99%
“…In contrast to the combined cues described by Bretman et al [11], Kim et al [15] reported that only one cue, vision, was needed for males to extend mating duration. Indeed it has been claimed that the only stimulus required is moving red eyes [15], though this is contested as further work was unable to replicate this result, and showed that males will not necessarily respond to heterospecific rivals with red eyes [16]. The cues important for behaviour to accurately react to environmental change will directly affect the mechanistic processes controlling behaviour [17].…”
Section: Introductionmentioning
confidence: 99%